Edit The effect of profitability, solvability and firm size on the audit delay on listed coal mining companies on the indonesia stock exchange - Mawadda Turahma; Kasmadi Kasmadi; Irfan Tanjung (STIE Bangkinang Publishing, 2022)
The purpose of this study was to determine the effect of profitability, solvency, and firm size simultaneously and partially on audit delay. This study in coal companies of subsektor listed on the Indonesia Stock Exchange in 2017-2020 period. The analysis used is multiple linear regression analysis with a sample of 15 coal companies. Hypothesis testing is done by f-test and t-test. The key is that simultaneously profitability, solvency, and firm size have a significant effect on audit delay partially. Of the three variables tested, only two variables have an effect on audit delay, namely profitability and firm size, while solvency has no effect on audit delay in coal sub-sector companies listed on the Indonesia Stock Exchange in 2017-2020 period. The closeness of the relationship between the independent variable and the variable is low with the independent contribution to the variable being 23.6%.